Gallivanting with Architecture - Julaihi, Wahid; Saleh, Basim; Chuloh, J; Abdullah, Azli (IOP Publishing Ltd, 2021)
Lately, it has been observed that buildings are becoming daring in their design, with forms and structures that appears to defy the law of gravity. The architecture discipline has been deployed to create eye-catching, even startling forms isolated in space that serves multiple purposes from authoritarian state-building to symbols of development, to "must-see" objects driving tourist to a particular place. These dramatic, monumental assemblies are not always well-received, however, with public outrage frequently directed toward their undesirable impacts on or lack of consideration toward the built context of a place. The building is not only a functional structure in any urban area but rather an intervention in the public space that remain there for many years or became an iconic landmark for someone to remember. The design of these buildings is not entirely based on the skill of the architect. Possibly influenced by the desires and tastes of the clients somewhat influenced by the practical constraints of the budget. Likewise, within those parameters, the creativity and even personality of the architect often shines through. The paper employed an exploratory techniques coupled with a descriptive analysis from printed materials as the framework to gather the written criticism of the projects that has been built. Through the pictorial and repertory grid applied in the investigation, this examines the essence of architecture design from the modern era until the present day. The findings from pictorial analysis showed that resemblance of the façade of the building symbolize the common objects and simple form found in daily life.